Responses of thenar muscles to transcranial magnetic stimulation of the motor cortex in patients with incomplete spinal cord injury. Issue 1 (1st July 1998) - Davey, Nick J; Smith, Hazel C; Wells, Elizabeth; Maskill, David W; Savic, Gordana; Ellaway, Peter H; Frankel, Hans L
Abstract : OBJECTIVE: To investigate changes in electromyographic (EMG) responses to transcranial magnetic stimulation (TMS) of the motor cortex after incomplete spinal cord injury in humans. METHODS: A group of 10 patients with incomplete spinal cord injury (motor level C3-C8) was compared with a group of 10 healthy control subjects. Surface EMG recordings were made from the thenar muscles. TMS was applied with a 9 cm circular stimulating coil centred over the vertex. The EMG responses to up to 50 magnetic stimuli were rectified and averaged. RESULTS: Thresholds for compound motor evoked potentials (cMEPs) and suppression of voluntary contraction (SVC) elicited by TMS were higher (p<0.05) in the patient group. Latency of cMEPs was longer (p<0.05) in the patient group in both relaxed (controls 21.3 (SEM 0.5) ms; patients 27.7 (SEM 1.3) ms) and voluntarily contracted (controls 19.8 (SEM 0.5) ms; patients 27.6 (SEM 1.3) ms) muscles. The latency of SVC was longer (p<0.05) in the patients (51.8 (SEM 1.8) ms) than in the controls (33.4 (SEM 1.9) ms). The latency difference (SVC−cMEP) was longer in the patients (25.3 (SEM 2.4) ms) than in the controls (13.4 (SEM 1.6) ms). CONCLUSION: The longer latency difference between cMEPs and SVC in the patients may reflect a weak or absent early component of cortical inhibition. Such a change may contribute to the restoration of useful motor function after incomplete spinal cord injury.